2020
DOI: 10.1136/bmjsem-2019-000677
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and exercise in youth mental health promotion: a scoping review

Abstract: Background/AimThis scoping review examined the breadth and outcomes of controlled trials testing the effect of physical activity and exercise interventions across all mental health outcomes for mental health promotion and indicated prevention studies in young people.MethodsThe literature search was conducted using ‘Evidence Finder’.ResultsThirty publications were included. Available evidence suggested that interventions of varying intensity may lead to a reduction in depression symptoms and that moderate-to-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
140
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(162 citation statements)
references
References 77 publications
9
140
0
13
Order By: Relevance
“…Eligible studies were either randomised controlled trials (RCT) or non-RCTs, published in English. Excluded studies were those that recruited people with specific physical, intellectual or mental disorder that were not the condition being treated with PA/exercise (eg, effects of exercise on depression in people with epilepsy); samples that had not been diagnosed with a mental disorder by a trained clinician or did not reach a defined cut-off score on a scale that indicated a likely disorder, as we have examined the impact of PA/exercise as a treatment for mental disorder in non-clinical samples in our companion paper to this article 28 ; dissertations; and studies published before 1980 as youth mental health was not considered a discrete field prior to 1980. 29…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Eligible studies were either randomised controlled trials (RCT) or non-RCTs, published in English. Excluded studies were those that recruited people with specific physical, intellectual or mental disorder that were not the condition being treated with PA/exercise (eg, effects of exercise on depression in people with epilepsy); samples that had not been diagnosed with a mental disorder by a trained clinician or did not reach a defined cut-off score on a scale that indicated a likely disorder, as we have examined the impact of PA/exercise as a treatment for mental disorder in non-clinical samples in our companion paper to this article 28 ; dissertations; and studies published before 1980 as youth mental health was not considered a discrete field prior to 1980. 29…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Increasingly larger studies have explored the relationship between physical exercise and individuals’ mental health, and some have found that physical exercise does improve mental health [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For example, Netz et al [ 17 ] determined that physical exercise has important beneficial effects on individuals’ physical and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract such detrimental consequences, the WHO encouraged people of all ages to "be active and stay healthy at home" [12]. It is well known that being physically active enables people to limit numerous risk factors for physical and mental diseases [13][14][15] and promotes individual's wellbeing [16]. Unfortunately, strong evidence reveals that the majority of children and adolescents in many countries do not participate in sufficient physical activity (PA) [17].…”
Section: Introductionmentioning
confidence: 99%